Gametogenesis in a dish - Gu, Ying (Nature Publishing Group, 2012)
Recent progress in the induced pluripotent stem cell (iPSC) field as well as the establishment of germline stem cell isolation and culture methodologies may provide an in vitro platform for the study of physiological and pathological human gamete development and open new avenues for cell replacement-based personalized treatment of infertility.